Impact of blood lipid levels on breast cancer prognosis: a systematic review and meta-analysis - Song, Jiaqing; Jin, Ying; Yu, Qinghong; Wu, Hongting; Gao, Xiufei (Frontiers in Oncology, 2025)
BackgroundBreast cancer has emerged as the predominant malignant neoplasm globally, with potential implications for patient prognosis based on blood lipid profiles. This study aims to systematically review and meta-analyze the influence of lipid levels on the prognostic outcomes of individuals with breast cancer.MethodsA thorough search was performed across multiple academic databases, including Embase, Cochrane, PubMed, Web of Science, CNKI, and Wanfang Database, up to March 2024. A meta-analysis was conducted to assess the impact of total cholesterol (TC), triglycerides (TG), low-density lipoprotein-cholesterol (LDL-C), and high-density lipoprotein-cholesterol (HDL-C) on the prognosis of Breast Cancer. The primary outcome measure was hazard ratios (HR) for overall survival (OS) and/or disease-free survival (DFS).ResultsEight studies meeting inclusion criteria from a total of 13,292 were included in the meta-analysis. The systematic review and meta-analysis demonstrate an association between lower HDL-C levels and poorer survival outcomes. However, the statistical analysis did not find significant associations between HDL-C, TG, and LDL-C levels and the prognosis of breast cancer patients.ConclusionWhile our analysis reveals a link between reduced HDL-C levels and unfavorable survival outcomes, the statistical evidence does not support significant connections between HDL-C, TG, and LDL-C concentrations and the prognostic landscape for breast cancer patients. Further research is warranted to explore these relationships more comprehensively.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42021297118.